EFL students responses towards Rosens Sad Book: An attitudinal occurrence and aesthetic stance - Anandari, Christina Lhaksmita; Andriyanti, Erna; Widodo, Pratomo (Universitas Syiah Kuala, 2024)
The vocabulary choice and language used in expressing sadness vary in different cultures, even in the smallest scale of cultural group, i.e., family. There have not been many studies done to explore Indonesian EFL students word choices and expressions related to expressing sadness and empathy. The purpose of this study was to explore how the 11 EFL second-year university students in Basic Reading and Writing class expressed sadness as written in their personal reflective writings. The data was analyzed using mixed methods to obtain valid and reliable results. These second-year university students were assigned to read a picture book, Sad Book, or to watch and listen to the video version as a part of an activity in class. Their reflective writings were analyzed using content analysis to identify the corpus used by the students and using the appraisal framework to capture the variety of their attitudinal linguistic occurrence in expressing sadness and empathy. The findings illustrate that the highest attitudinal marker in expressing sadness is affect, followed by judgment and appreciation. The use of the picture book, Sad Book, assists the EFL students to be more engaged in their reflective writing and thus the highest marker of affect exists due to their ability to project their aesthetic stance. Implications for English language learning for adult learners are addressed at the end of this article.